Strategi Manajemen Peningkatan Mutu Peserta Didik: Menjembatani Spiritualitas Dan Digitalisasi di Sekolah Dasar Negeri - Nur Aini, Intan; Romadhoni, Makbul; Umi Khoiroh, Anisya; Juhairiyah, Juhairiyah; Nurhadi, Ali (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2025)
This study aims to describe the quality improvement management strategy for students through the integration of Islamic spiritual values and digital approaches at SDN Bulangan Barat. Employing a descriptive qualitative method, data were collected through observations, interviews with the principal and teachers, as well as discussions with students. The findings reveal that the school implements a value-based quality management strategy by utilizing interactive digital media that still conveys moral and religious messages. This integration is well-received by students, who tend to favor visual and digital learning. Despite challenges such as limited technological resources and teacher readiness, the school addresses these issues through innovative programs, training, and internal collaboration. The study concludes that effective quality management in education during the digital era can be achieved without compromising spiritual identity; instead, spirituality can serve as a core strength in shaping students’ character.